Do Compulsory Schooling Laws Affect Fertility Behaviors and Marriages? Evidence from India - Sandipa Bhattacharjee (Global Labor Organization (GLO), 2025)
This paper exploits an education policy in India generated by a 2010 schooling reform to examine the effect of education on women's family planning decisions. The key element of the reform was that it required students to complete eight years of primary education (age 6-14 years). I employ an instrumental variable difference-in-difference approach that mea- sures the exogenous variation in treatment intensity in different states across birth cohorts of women measured by birth year and birth months. The reform led to an increase in total years of education, a delay in the age at first marriage, a postponement of sexual activity, and reduced fertility beginning at the age of 22. I also examine the potential mechanisms through which increased education affects fertility. The findings suggest early use of modern contraceptives, reduction in the marital education gap, increased literacy, and utilization of healthcare services contribute to reduced fertility. These results are consistent with the in- creased empowerment of women influencing their fertility decision thereby highlighting the importance of the government's efforts to promote education through policy initiatives.
Keywords: I25; J13; J18; 330; education; fertility; India